THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING FOREIGN LANGUAGE - Khan Suliman (Galaxy International Interdisciplinary Research Journal, 2023)
This article contains thoughts and opinions about artificial intelligence, which is expected to be one of the greatest discoveries of the 21st century, and its importance in learning a foreign language.